Application of mobile nursing system based on 5G technology in clinical blood transfusion management (基于5G技术的移动护理系统在临床输血护理管理中的应用) - HUANG Liming (黄丽明); LI Chunrong (李春容) (中西医结合护理)
Objective To evaluate the mobile nursing system based on 5G technology in clinical blood transfusion management. Methods The clinical data of 192 patients (control group) who underwent clinical blood transfusion between Jan 2022 and December 2023 were retrospectively analyzed, and their information during the blood transfusion process were manually checked. The mobile nursing system based on 5G technology had been adopted in in clinical blood transfusion management since Jan 2024, and clinical data of 212 patients (observation group) who underwent clinical blood transfusion between Jan 2024 and Jan 2025 were analyzed. The rate of double-checking bedside collection of blood samples, implementation rate of double-checking bedside blood transfusion, rates of inspection 15 minutes after blood transfusion and per hour were compared between two groups, and defects in nursing records of two groups were analyzed. Results After adopting the 5G technology in clinical blood transfusion management, there were remarkable increases in rate of double-checking bedside collection of blood samples, implementation rate of double-checking bedside blood transfusion, rates of inspection 15 minutes after blood transfusion and per hour, with a significant difference (P＜0. 05). The incidence of nursing records defects in the observation was lower than that in the control group (P＜0. 01). Conclusion The 5G technology-based mobile nursing system can standardize the blood transfusion process, conduct precise scanning and verification, achieve closed-loop management of the nursing process, enhance the efficiency of nurses, improve the quality of blood transfusion care, and ensure the safety of clinical blood transfusion. (目的 探讨基于5G技术的移动护理系统在临床输血护理管理中的应用效果。方法 回顾性分析胃肠外科病区2022年1月—2023年12月接受临床输血的192例患者的临床资料, 设为对照组, 输血采用人工核对输血操作中的各项信息; 选取2024年1月—2025年1月采用基于5G技术的移动护理系统后接受临床输血212例患者, 设为观察组, 输血利用5G技术、条形码、移动终端等技术进行输血闭环管理。比较两组血标本采集床边双人核对率、床边输血双人核对执行率、输血后15min及每小时巡视率, 以及输血护理记录缺陷情况。结果 实施基于5G技术的移动护理系统后, 血标本采集床边双人核对率、床边输血双人核对执行率、输血后15min及每小时巡视率, 均高于实施前(P＜0. 01); 观察组输血护理记录缺陷发生率低于对照组(P＜0. 01)。结论 基于5G技术的移动护理系统应用于临床输血护理管理中, 能够规范输血流程, 精细扫码核对, 实现护理流程闭环管理, 提高护士工作效率, 提高了输血护理质量, 确保临床输血安全。)